Contrasting Deontological Economics with an Islamic Economics - Mansur, Ahmad (OECONOMICUS Journal of Economics, 2022)
Deontological economics is a value-based approach to economics which is originated and inspired by Kant’s deontological theory of ethics. It has come to us to challenge the mainstream economics by proposing the view that economics is not value free. It views that ethical value plays an important role in economics, and ethics must be incorporated in economics. Exploring this economic school of thought is very interesting. It will present a new nuance, in the sense that economics will not get into the right path, if it does not know about ethics and does not practice it. It warns the mainstream economics that economics is not only about maximization of profit and satisfaction, but it is about the realization of value.Since Deontological economics and Islamic economics both proclaim that morality and ethical values cannot be separated from economy, as they will guide human behaviour in their doing economy to achieve social bliss, happiness and social harmony as well as their economic development, this research tries to discuss and investigate the incorporation of ethical values both in Islamic and in Deontological economics.The ethical value advocated by Deontological economics of human existence in this world such as to prosper on earth and to heal the world to make it better place to seek the pleasure of God and to keep the balance in economy between satisfying individual needs and social needs, and between satisfying material needs and spiritual needs, to respect others, to preserve the human’s dignity and many other values which are similar or even the same as that of what Islamic economics advocates is very interesting and it is worth to have our attention and discussion. Despite the ethical value of an Islamic economics is departing from the Quran and the Sunnah, this research comes to the conclusion that there existed similarity between both of them or even the same, except the value of usury (riba). Another outcome is that both of them could be grounded in the real economic activities, and it is not merely theoretical construct.